A prevalence study on the hepatitis B carrier state and hepatitis C virus infections among inmates at Camp Sampaguita, Bureau of Corrections, Muntinlupa, M.M. - Alipio, Arlene E. (1995)
The prevalence of Hepatitis B virus carrier state and Hepatitis C virus infection was determined in 502 inmates at Camp Sampaguit, Bureau of Prisons, Muntinlupa. HBsAg positivity, a measure of HBV carrier rate, as determined by Enzyme Immunoassay or EIA (Auszyme by Abbott) was 12.9. The prevalence of HCV infection, indicated by the presence of antibodies against HCV and tested using the Enzyme Linked Immunosorbent assay or ELISA (Monolisa anti-HCV by sanofi Diagnostics Pasteur) was 5.0. Of the study population, 0.4carry both hepatitis markers. ALT levels were taken and found to be associated with HCV infection but not with HBV carrier state.All subjects were interviewed to gather information on the possible factors associated with acquiring HBV and/or HCV infections. The practice of homosexual activities and parenteral drug use were two risk factors found to be significantly associated with HCV infection but not with HBV carrier state. The anti-HCV prevalence among the subjects with these 2 risk factors were 12.9and 35.0, respectively.There were also factors which became assocaited with HBV carrier state and HCV infection when the factor has been done both prior to and during incarceration; that is, homosexual activities for HBsAg and the practice of "paandar" for HCV infection. Clearly, incarceration may contribute in increasing the risk of acquiring these infections.The prevalence of anti-HCV was consistently higher among those with tattooes, who had blood transfusion, ears pierced, with "bulitas" implants and self-inflicted "paandar", but the prevalence were not significant when compared with the group without the said factors. Generally, the period of incarceration, tattooing, blood transfusion, ear piercing, implantation of "bulitas" and the pratice of "paandar" were all not associated with acquiring either or both hepatitis viruses.A further study to determine the baseline data on HCV infection in the general population is suggested to determine the magnitude of the disease and for basis of comparison. A prospective cohort study is also recommended to better establish the association of the behavioral and other factors with HBV or HCV infections.In conclusion, the inmates at the Education Section of Camp Sampaguita maybe considered a potential risk group for acquiring HCV infection because of the high prevalence of anti-HCV; but not for HBV infection since the prevalence of HBsAg was about as high as the prevalence of the general population. They may be possible reservoirs of Hepatitis C virus because of their habits and lifestyle which are potential factors for transmitting this agent.
Thesis (Master of Science in Public Health)--University of the Philippines Manila.
Keywords: Hepatitis B; Hepatitis C